2017
DOI: 10.18632/oncotarget.15633
|View full text |Cite
|
Sign up to set email alerts
|

YEATS4 promotes the tumorigenesis of pancreatic cancer by activating beta-catenin/TCF signaling

Abstract: Beta-catenin/TCF signaling has been reported to promote the growth and metastasis of pancreatic cancer cells. However, the regulation for the beta-catenin/TCF transcriptional complex remains largely unknown. Here, we have found that YEATS4 is a positive regulator for Beta-catenin/TCF signaling. The expression of YEATS4 was elevated in clinical pancreatic cancer samples and pancreatic cancer mouse model. Up-regulation of YEATS4 promoted the growth, migration and invasion of pancreatic cancer cells, while knocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…YEATS4 transcript overexpression was noted in 31 pancreatic cancer samples relative to adjacent noncancerous tissues (Jixiang et al, 2017). An expansion of this study to 93 pancreatic samples in the ONCOMINE database (Rhodes et al, 2004) further indicated clinical significance of YEATS4 expression in pancreatic cancer.…”
Section: Pancreatic Cancermentioning
confidence: 64%
See 3 more Smart Citations
“…YEATS4 transcript overexpression was noted in 31 pancreatic cancer samples relative to adjacent noncancerous tissues (Jixiang et al, 2017). An expansion of this study to 93 pancreatic samples in the ONCOMINE database (Rhodes et al, 2004) further indicated clinical significance of YEATS4 expression in pancreatic cancer.…”
Section: Pancreatic Cancermentioning
confidence: 64%
“…Further evidence for a function of YEATS4 in transcription has come from direct interactions with transcription factor TFAP2A (AP-2) (Ding et al, 2006), and the C-terminal region of the myc family members MYCN and MYC (Piccinni et al, 2011), identified by affinity capture techniques such as yeast two-hybrid analysis, GST-pull down and coimmunoprecipitation. The β-catenin gene (CTNNB1) is regulated by binding of YEATS4 to its promoter, either via these transcription factors, or in combination with the chromatin modeling complexes discussed above (Ji et al, 2017;Jixiang et al, 2017). Downstream targets of β-catenin such as CCND1 (Cyclin D1), CDK4, CDK6 and c-Myc, and the apoptotic proteins BCL2 and BAX also respond to overexpression and decreased expression of YEATS4 in gastric cancer and pancreatic cancer (Ji et al, 2017;Jixiang et al, 2017).…”
Section: Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although surgery is the primary way of treatment, pharmacological treatments are also an important adjuvant to surgery. During the past decades, studies have tried to understand the undelying molecular and signaling mechanisms that regulate the development of PC so that better therapy strategies may be developed ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%